Porous Silicon–Based Microring Resonator for Temperature and Cancer Cell Detection - Gangwar, Rahul Kumar; Qin, Jun; Wang, Xingjun (Frontiers in Physics, 2022)
In this paper, a microring resonator sensor based on the porous silicon is proposed for the temperature and cancer cell detection, simultaneously. The porous behaviour with large internal surface area of the silicon allows external materials interact directly with the guided modes. The resonance wavelength in the transmission spectrum of the microring resonator is very sensitive to the external environment properties such as refractive index and temperature. The transmission characteristics of the proposed sensor were numerically analysed by using full vectorial finite element analysis. The achieved maximum sensitivity of the proposed sensor with optimised parameters are 150 pm/°C for the operational temperature range of 20°C - 100°C and 284.0306 nm/RIU for the operational cancer cell detection, respectively. The results present here are promising in the fields of environment sensing, temperature sensing, chemical and biosensing.